2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30897
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development for High School Guidance Counselors to Facilitate Pre-college STEM Preparation (RTP)

Abstract: is a high school physics teacher and Ph.D. candidate in the Institute for STEM Education at Stony Brook University. He attended Buffalo State College where he received his B.S. and M.S. degrees in physics education. He was appointed a New York State Master Teacher in 2014. His research interest is in identifying and reducing barriers to STEM education opportunities for all students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Common constraints include student–counselor caseloads, numbers of counselors, and college‐specific guidance and counseling provided through designated college counselors, advisors, mentors, or coaches (Bryan et al., 2009; Poynton & Lapan, 2017; Shi & Brown, 2020). Two qualitative studies revealed that constraints such as large caseloads and little designated time for CCR counseling limit school counselors from fully supporting students in the college‐going process (Gearns, Kelly, & Bugallo, 2018; Shillingford, Oh, & Finnell, 2017). Also, in a number of studies using national datasets, both counselor caseload and number of counselors affect the provision of school counseling services and students’ academic outcomes and college application and enrollment rates (Bryan et al., 2011; Engberg & Gilbert, 2014; Fitzpatrick, 2019; Goodman‐Scott et al., 2018; Poynton & Lapan, 2017; Rangel & Ballysingh, 2020; Shi & Brown, 2020; Woods & Domina, 2014).…”
Section: Conceptual Framework: Operationalizing School Counseling College‐going Culturementioning
confidence: 99%
“…Common constraints include student–counselor caseloads, numbers of counselors, and college‐specific guidance and counseling provided through designated college counselors, advisors, mentors, or coaches (Bryan et al., 2009; Poynton & Lapan, 2017; Shi & Brown, 2020). Two qualitative studies revealed that constraints such as large caseloads and little designated time for CCR counseling limit school counselors from fully supporting students in the college‐going process (Gearns, Kelly, & Bugallo, 2018; Shillingford, Oh, & Finnell, 2017). Also, in a number of studies using national datasets, both counselor caseload and number of counselors affect the provision of school counseling services and students’ academic outcomes and college application and enrollment rates (Bryan et al., 2011; Engberg & Gilbert, 2014; Fitzpatrick, 2019; Goodman‐Scott et al., 2018; Poynton & Lapan, 2017; Rangel & Ballysingh, 2020; Shi & Brown, 2020; Woods & Domina, 2014).…”
Section: Conceptual Framework: Operationalizing School Counseling College‐going Culturementioning
confidence: 99%
“…Teacher participants improved their confidence in informing students about engineering careers, precollege preparatory coursework, and differentiating among engineering disciplines. This may be consequential for students since STEM career advisement has often been lacking with school counselors (Gearns et al 2018;Gibbons et al 2003), and STEM teachers may be influential through serendipitous conversations, personal encouragement, and an increased emphasis on the relevance of engineering in devising technological solutions (Packard and Jeffers 2013).…”
Section: Affective Impacts On Engineering Preparation and Careersmentioning
confidence: 99%
“…This may include the development of “counterspaces” for women of color and underrepresented groups within STEM high school departments to counteract feelings of isolation where students with shared experiences can seek out support without fear of marginalization . Schools and districts might examine the science classroom climate more closely and train teachers in promoting culturally responsive pedagogical practices; such practices include positive encouragement from mentors and teachers, critical feedback, , proactive STEM academic advisement, and emphasizing the sociocultural relevance of chemistry …”
Section: Discussionmentioning
confidence: 99%